English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

(a)SIN A-TAN A
(b)SIN A-COSEC A
(c) COS A + SEC A
(d)COSEC A-SIN A

explain it clearly.

2007-04-05 07:20:00 · 3 answers · asked by RiNkU 1 in Science & Mathematics Mathematics

3 answers

The sum of the roots is the opposite of the middle term of the quadratic. In this case: - cot(A)*cos(A).

Now use some trig identities: -cos^2(A)/sin(A) = -(1 - sin^2(A))/sin(A) = -csc(A) + sin(A).

So the answer is (b).

A very odd question...

2007-04-05 07:28:51 · answer #1 · answered by tedfischer17 3 · 0 0

The sum of the roots of a quadratic equation ax^2+bx+c=0 is simply -b/a.
In your equation a = 1 and b= cotAcosA
Thus sum of roots = - cotAcosA

This is not one of the given answers, so either your book is wrong, or you have made a mistake in writing the problem.

2007-04-05 07:38:08 · answer #2 · answered by ironduke8159 7 · 0 0

sin x cos x-sin x -cos x + a million=0 sinx(cosx-a million) - (cosx-a million)=0 (cosx-a million)(sinx-a million)=0 cosx-a million =0 or sinx-a million=0 cosx = a million or sinx = a million x = 2n? or x = n? +(-a million)^n (?/2) ; n = 0,a million, 2, 3, ... Sustitute for n & discover for x interior of 0?x?? whilst n=0 ; x = 0, ?/2 interior of 0?x?? Now you will see the answer

2016-12-15 17:04:52 · answer #3 · answered by ? 4 · 0 0

fedest.com, questions and answers